Hybrid, electric and fuel-cell vehicles - Erjavec, Jack (Delmar Cengage Learning, 2013)
Author Jack Erjavec combines in-depth industry expertise with an engaging, reader-friendly style, providing extensive detail on new and upcoming electric vehicles, including hybrids in production today and the fuel cell vehicles of tomorrow. Expansive coverage ranges from basic theory related to vehicle construction, electricity, batteries, and motors, to the political and social impact of these high-profile vehicles. In addition to up-to-date, highly accurate technical information on vehicles available today-including service procedures and safe shop practices-the text provides an informed look into the future with material on vehicles currently under development.